An analytical model for a liquid plug moving in curved microchannels - Che, Zhizhao (2012)
Droplet-based microfluidics has wide applications and triggers numerous researchers’ interest. It is significant to study the flow field inside a droplet moving in microchannels. This paper presents an analytical method to investigate the flow field inside a confined droplet (a plug) moving in curved microchannels with high aspect ratio. The flow field is compared against a one-dimensional solution and the published experimental data. The effects of the plug length and the curvature on the flow pattern and the flow resistance are studied. The results suggest that the vortex pattern of the plug can be controlled by designing the channel geometry.